94.6k views
2 votes
Arrange the steps to solve the equation square root x+3 - square root 2x-1=-2

User Hyla
by
4.7k points

1 Answer

3 votes

Answer:x=31.4919

Explanation:

Step1:isolate a square root on the left hand side√x+3=√2x-1-2

Step2:eliminate the radicals on the left hand side

Raise both sides to the second power

√x+3)^2=(√2x-1-2)^2

After squaring

x+3=2x-1+4-4-4√2x-1

Step3:get the remaining radicals by itself

x+3=2x-1+4-4√2x-1

Isolate radical on the left hand side

4√2x-1=-x-3+2x-1+4

4√2x-1=x

Step4:eliminate the radicals on the left hand side

Raise both side to the second power

(4√2x-1)^2=x^2

After squaring

32x-16=x^2

Step 5:solve the quadratic equation

x^2-32x-16

This equation has two real roots

x1=32+√960/2=31.4919

x2=32-√960/2=0.5081

Step6:check that the first solution is correct

Put in 31.4919 for x

√31.4919+3=√2•31.4919-1-2

√34.492=5.873

x=31.4919

Step7:check that the second solution is correct

√x+3=√2x-1-2

Put in 0.5081 for x

√0.5081+3=√2•0.5081-1-2

√3.508=-1.873

1.873#-1.873

One solution was found

x=31.4919

User Aaron Qian
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.